2021
DOI: 10.3389/fonc.2021.683768
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of N6-methyladenosine (m6A) Modification in Osteosarcoma

Abstract: Osteosarcoma is the most common primary bone malignancy, typically occurring in childhood or adolescence. Unfortunately, the clinical outcomes of patients with osteosarcoma are usually poor because of the aggressive nature of this disease and few treatment advances in the past four decades. N6-methyladenosine (m6A) is one of the most extensive forms of RNA modification in eukaryotes found both in coding and non-coding RNAs. Accumulating evidence suggests that m6A-related factors are dysregulated in multiple os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 106 publications
(187 reference statements)
0
10
0
Order By: Relevance
“…m6A modification is closely related to the occurrence and development of cancer and participates in cell differentiation, proliferation, migration, immunity, and drug resistance. Deregulation of m6A regulators in OS is inevitable [ 11 , 13 , 30 , 31 ]. Miao et al reported that METTL3 contributes to proliferation, migration, and invasion of OS cells and activates the Wnt/β-catenin signaling pathway by regulating m6A modification of LEF1 mRNAs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…m6A modification is closely related to the occurrence and development of cancer and participates in cell differentiation, proliferation, migration, immunity, and drug resistance. Deregulation of m6A regulators in OS is inevitable [ 11 , 13 , 30 , 31 ]. Miao et al reported that METTL3 contributes to proliferation, migration, and invasion of OS cells and activates the Wnt/β-catenin signaling pathway by regulating m6A modification of LEF1 mRNAs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALKBH5 attenuates the m6A modification of PVT1 mRNA and impedes the binding of YTHDF2 to PVT1 mRNA, which increases PVT1 expression and accelerates OS growth in vivo [ 13 ]. In addition, m6A-related enzymes are involved in regulating the pluripotency of OS stem cells [ 31 , 32 ]. All these imply potential roles of m6A methylation in tumorigenesis and progression of OS.…”
Section: Discussionmentioning
confidence: 99%
“…OS attacks the musculoskeletal system, causing joint pain, swelling, muscle atrophy, joint dysfunction and even pathological fracture 179 . OS has a high degree of heterogeneity and significant genome complexity, and the pathophysiology remains unclear 180 . The mutual regulation between m6A and miRNA/circRNA/lncRNA is found in OS and is involved in the growth, migration, invasion of tumour cells, tumorigenesis and tumour progression 34,37,181 .…”
Section: Interplay Between M6a and Ncrna In Msdsmentioning
confidence: 99%
“… 179 OS has a high degree of heterogeneity and significant genome complexity, and the pathophysiology remains unclear. 180 The mutual regulation between m6A and miRNA/circRNA/lncRNA is found in OS and is involved in the growth, migration, invasion of tumour cells, tumorigenesis and tumour progression. 34 , 37 , 181 The major mutual regulation mechanism between miRNA and m6A in OA is that m6A accelerates pri‐miRNA processing and maturation.…”
Section: Interplay Between M6a and Ncrna...mentioning
confidence: 99%
“…Numerous investigations have revealed that methylation modifications extensively regulate osteosarcoma proliferation, apoptosis, migration, invasion, and tumor microenvironment [30] , [31] , [32] . Furthermore, aberrant expression of methylation modification regulators is intimately correlated with poor prognosis and chemotherapy resistance in osteosarcoma [30] , [33] . Although the functions and mechanisms of RNA modifications have been identified in the complex epigenomic and transcriptomic environment of osteosarcoma, the biological significance and essential target genes of m7G regulators in osteosarcoma remain elusive to date.…”
Section: Introductionmentioning
confidence: 99%